Lectures patrimoniales du thermalisme : quand le patrimoine culturel immatériel et le patrimoine architectural et paysager se nourrissent réciproquement - Mathilde Lamothe (Les Cahiers de Framespa)
Until recently, the inventories of France’s intangible cultural heritage and those of the General Inventory of Cultural Heritage had rubbed shoulders without ever really meeting, just like the people taking the waters in the Pyrenees in the 19th century. The European research programme TCV-PYR, dealing with an inventory of the thermal and holiday heritage in the Pyrenees, brought together researchers from multiple scientific disciplines (history, art history, geography, and anthropology) using different methodologies in order to carry out these heritage inventories. This article summarises what was said during a round-table discussion with these researchers and the questions they asked each other despite their different heritage sensitivities. The challenge is to create a dialogue between these forms of heritage from a scientific but also digital point of view, using the databases developed by the Inventory and Intangible Cultural Heritage departments.